PERKECAMBAHAN, PERAKARAN DAN PERTUMBUHAN HIPOKOTIL BENIH KOPI ARABIKA VARIETAS CATUAI PADA APLIKASI BERBAGAI KONSENTRASI GIBERELLIN ACID (GA3) - Muhammad Kadir; Image Rainy Clarita; Syatrawati Syatrawati; Nur Amalika Sagita (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2020)
The mass propagation of coffee plants requires seeds with high-viability characterized by good germination and germination growth. One way to increase the viability of coffee seeds is the provision of Gibberellic acid (GA3). This study aims to determine the effect of several concentrations of GA3 on the viability of Catuai variety of Arabica coffee. The experiment used a completely randomized design (CRD). Treatment with Control and 5 levels of GA3 concentration, namely 0 (Control), 100, 200, 300, 400 and 500 ppm respectively where coffee seeds were soaked for 24 hours before being germinated. The results showed that the concentrations of 300 and 200 ppm GA3 showed the best results for germination percentage and rate Germination, however, did not appear to have a significant effect on the root and hypocotyl length.